2019
DOI: 10.1002/ange.201904722
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots as a New Class of Diamagnetic Chemical Exchange Saturation Transfer (diaCEST) MRI Contrast Agents

Abstract: While carbon dots (C-dots) have been extensively investigated pertaining to their fluorescent, phosphorescent, electrochemiluminescent, optoelectronic,and catalytic features, their inherent chemical exchange saturation transfer magnetic resonance imaging (CEST MRI) properties are unknown. By virtue of their hydrophilicity and abundant exchangeable protons of hydroxyl, amine,a nd amide anchored on the surface,wereport here that C-dots can be adapted as effective diamagnetic CEST (diaCEST) MRI contrast agents.A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Recent work demonstrated that the abundant exchangeable protons from the surface functional groups of g-N-CDs are inherently CEST-MRI-detectable. 134 g-N-CDs exhibited appreciable CEST-MRI contrast, which was attributed to the abundant exchangeable hydroxyl and guanidinium protons on the CD surface derived from the glucose and arginine precursors. This example points to further advances of CDs as CEST-MRI contrast agents because the variety of functional groups commonly found on the CD surface usually contains exchangeable protons, and the nature of these groups can also be easily controlled through pre-synthetic design.…”
Section: Towards Biomedical Applicationsmentioning
confidence: 99%
“…Recent work demonstrated that the abundant exchangeable protons from the surface functional groups of g-N-CDs are inherently CEST-MRI-detectable. 134 g-N-CDs exhibited appreciable CEST-MRI contrast, which was attributed to the abundant exchangeable hydroxyl and guanidinium protons on the CD surface derived from the glucose and arginine precursors. This example points to further advances of CDs as CEST-MRI contrast agents because the variety of functional groups commonly found on the CD surface usually contains exchangeable protons, and the nature of these groups can also be easily controlled through pre-synthetic design.…”
Section: Towards Biomedical Applicationsmentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. d Schematic illustration of the cellular uptake of AC-dots following liposome encapsulation (Reprint with permission [ 95 ]. Copyright 2019, WILEY–VCH) …”
Section: Mrimentioning
confidence: 99%
“…3 c). In addition to organic nano Cas, hydrophilic carbon dots were also demonstrated to produce CEST signals due to the abundance of exchangeable protons on the surface [ 95 ]. The carbon dots were obtained through a microwave-assisted synthesis method with glucose as the carbon source and arginine as the hydrophilic modification molecules.…”
Section: Mrimentioning
confidence: 99%
“…8a). 105 They encapsulated AC-dots with liposomes (Lipo-AC-dots) to increase the cellular uptake of AC-dots (Fig. 8b).…”
Section: Carbon Dots As Magnetic Resonance Imaging Probesmentioning
confidence: 99%